2022
DOI: 10.1111/ijfs.15736
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of interactions between egg protein–derived tri‐peptides and cellular membrane by molecular dynamic simulation and isothermal titration calorimetry

Abstract: Summary Poor understanding of the absorption of food‐derived angiotensin‐converting enzyme (ACE) inhibitory peptides across the membrane limits their application in regulating and preventing hypertension. This study investigated the interaction of egg‐derived ACE inhibitory tri‐peptides ADF, FGR and MIR with the membrane using molecular dynamic simulation and isothermal titration calorimetry (ITC). The structural variations in peptides during absorption were analysed. The effect of peptides on the properties o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…The peptides were synthesised using the solid-phase process by a previously described method (Yuan et al, 2021;Yu et al, 2021aYu et al, , 2021bJi et al, 2022aJi et al, , 2022b.…”
Section: Peptide Synthesismentioning
confidence: 99%
“…The peptides were synthesised using the solid-phase process by a previously described method (Yuan et al, 2021;Yu et al, 2021aYu et al, , 2021bJi et al, 2022aJi et al, , 2022b.…”
Section: Peptide Synthesismentioning
confidence: 99%
“…2 A large number of egg-white-derived ACE inhibitory peptides have been identified, i.e. IRW, 3 ADF, 4 FGR, 5 RVPSL, QIGLF 6,7 and TNIIGR, 8 which have the potential to prevent or treat hypertension. 9 Our previous studies have shown that the egg-white-derived ACE inhibitory peptide RVPSL could significantly lower the blood pressure (BP) of spontaneously hypertensive rats (SHRs) in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…The RMSD of the α-carbon atoms for NCW (Figure 1) deviated only slightly from the starting conformation throughout the simulation and showed stability oscillating around ∼0.07 Å, which suggested that the simulated system had reached an equilibrium state and the structure of NCW was highly stable in the presence of DPPC membranes. Fluctuations in structures were more obvious for NCW (0.01-0.17 nm) than tripeptide ADF (0.01-0.15 nm) and MIR (0.02-0.14 nm) reported in the previous study by Ji et al (6), indicating that tripeptide NCW had good flexibility during absorption into the bilayer.…”
Section: Peptide Structural Properties Across the Cellular Membranementioning
confidence: 51%